2018
DOI: 10.1039/c7ce02014g
|View full text |Cite|
|
Sign up to set email alerts
|

In situ growth of ZnO/SnO2(ZnO:Sn)m binary/superlattice heterojunction nanowire arrays

Abstract: This work presents a novel growth design of an in situ epitaxially grown SnO2(ZnO:Sn)m superlattice segment on top of ZnO nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Without the use of proper analytical methodology and failing to study the previous work on Sn-rich IBs, Cao et al [55] concluded that IBs in their SnO 2 (ZnO:Sn) m nanowires are fully occupied by Sn. Similar conclusions were drawn a year later by Park et al [56], followed by three further studies [57][58][59], where Tan et al [59] nicely shows an intensity undulation in HAADF-STEM image indicating that the IB-layer is probably not fully occupied by Sn. On the other hand, it is great to read the studies by Eichhorn et al [60] and Hoemke et al [63] that have built on this knowledge and constructed fascinating modulated structures with parallel Sn-rich basal-plane IBs making use of either Ga 2 O 3 or Al 2 O 3 additions to stabilize the transient tail-to-tail configuration inbetween, respectively.…”
Section: Local Chemistry Of the Sn-rich Ibssupporting
confidence: 71%
See 4 more Smart Citations
“…Without the use of proper analytical methodology and failing to study the previous work on Sn-rich IBs, Cao et al [55] concluded that IBs in their SnO 2 (ZnO:Sn) m nanowires are fully occupied by Sn. Similar conclusions were drawn a year later by Park et al [56], followed by three further studies [57][58][59], where Tan et al [59] nicely shows an intensity undulation in HAADF-STEM image indicating that the IB-layer is probably not fully occupied by Sn. On the other hand, it is great to read the studies by Eichhorn et al [60] and Hoemke et al [63] that have built on this knowledge and constructed fascinating modulated structures with parallel Sn-rich basal-plane IBs making use of either Ga 2 O 3 or Al 2 O 3 additions to stabilize the transient tail-to-tail configuration inbetween, respectively.…”
Section: Local Chemistry Of the Sn-rich Ibssupporting
confidence: 71%
“…Similar conclusions were made by other authors [53,54]. Observation of IBs in Sn-doped ZnO nanobelts and nanowires was followed by highly competitive studies of their atomic structure using scanning transmission electron microscopy (STEM) methods [55][56][57][58][59]. While most of these studies correctly interpret the translation state of Sn-rich IBs, their lack in understanding of the local charge balance [15] is reflected in erroneous interpretation of the occupancy and arrangement of Sn atoms in the IB-plane.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations